Survey on children with cerebral palsy in Tochigi Prefecture, Japan. Issue 8 (30th June 2021) - Yamagishi, Hirokazu; Osaka, Hitoshi; Toyokawa, Satoshi; Kobayashi, Yasuki; Shimoizumi, Hideo
Abstract: Background: The incidence of cerebral palsy (CP) is influenced by perinatal medicine and regional medical systems. We investigated the recent incidence of CP and the current problems of children with CP in living at home under an advanced perinatal medical system in Tochigi Prefecture, Japan. Methods: A clinical datasheet survey was performed among 13 hospitals and six rehabilitation facilities treating children with CP born in Tochigi Prefecture to estimate the incidence of CP among children born between 2009 and 2013. The severity of motor and intellectual impairment, presumed causal factors, complications, and provided medical interventions were investigated and compared between preterm and term‐born children with CP. Results: The incidence of CP was 1.6 per 1000 live births. Shorter gestation period and lower birthweight were associated with a higher incidence of CP. Fifty‐one percent of children with CP were non‐ambulatory and 55% had severe to profound intellectual impairment. Episodes of neonatal asphyxia and periventricular leukomalacia were the most frequent causal factors; both were significantly more frequent in preterm than in term‐born children. Approximately 30% of children with CP had respiratory disorders, dysphagia, or epilepsy; 62% received medical interventions, including medication, mechanical ventilation, oxygen therapy, tube feeding, and intraoral/intranasal suction. Conclusion: We found the incidence of CP to be lower in comparison to previous Japanese studies. However, the motor and intellectual impairments were severe, and many children with CP and their families were burdened by daily medical care. Public support systems should be developed, as well as the perinatal medical system.